Firm Reputation, Firm Resource Endowment, and Circular Economy Entrepreneurship: The Mediating Role of Managerial Commitment - Rijal, Anita (Nepalese Journal of Insurance and Social Security, 2024)
Purpose: Environmental demands in today’s era have initiated circular economy (CE) initiatives to improve their reputation and provided a platform to exploit CE opportunities and develop circular economy entrepreneurship (CEE). While extant CE literature asserts that resources and managerial commitment (MC) are crucial for greater circular outcomes, studies that explore how firm reputation (FR) can promote a firm resource endowment (FRE) for enhanced CEE while investigating the mediating influences of MC are lacking. Bridging this gap, this study using the resource-based view investigates theassociations between FR, FRE, MC, and CEE in the context of Nepal.Design/methodology/approach: This study used a survey research design to collect data from managers of manufacturing SMEs and analysed it using partial least square structural equation modelling (PLS_SEM).Findings: The results indicated that FR has a significant impact on FRE, MC, and CEE. The findings particularly indicate that FRE and MC have a significant impact on CEE. However, the impact of FRE on MC is not significant. Furthermore, while it was observed that MC served as a mediating role in the connection between FR and CEE, there was no evidence of mediation between FRE and CEE.Conclusion: By leveraging FR and FRE, manufacturing SMEs in Nepal can promote CEE. In addition, firms enjoying superior reputations from the implementation of CE practices are likely to motivate managers’ commitment to CEE that ensure sustainability.Implications: The results highlight the theoretical and practical implications useful for scholars, policymakers, and managers.JEL Classification: D22, L26, M14, Q46